Diversity of Industrially Important Hydrolytic Enzymes Explored in Bacteria from Aquatic Environment - Razzaq, Saima; Dilshad, Rimsha; Batool, Rida; Jamil, Nazia (Polish Journal of Natural Sciences, 2023)
Aquatic bacteria are famous for the production of bioactive metabolites and commercially important extracellular enzymes. Water samples of Arabian Sea (Karachi) and Ravi River (Lahore), Pakistan were analyzed for hydrolytic enzymes producing bacteria. A total of 23 bacterial strains were isolated and their α-amylase, DNase, gelatinase, L-glutaminase, pectinase, lecithinase and protease production potential was estimated. Following screening, 11 strains (48%) showed amylase activity whereas DNase and gelatinase was produced by 5 stains (22%) and 18 strains (78%), respectively. L-glutaminase and pectinase production was shown by 17 isolates (74%) while lecithinase and protease activity only exhibited in 2 (13%) and 1 strain (4%), respectively. Ribotyping of five selected (S5, S6, H4, H5 and R8) isolates revealed their similarity to B. tequilensis, B. pumilus, B. flexus, B. sonorensisa and B. subtilis. These isolates also showed multiple heavy metal and antibiotic resistance. This indigenous Bacillus spp. hold great potential to be utilized as commercial strains provided with optimum growth conditions. Extracellular enzymes of these bacterial strains can be utilized in different industries, agriculture and bioremediation purposes to replace synthetic components.